2015
DOI: 10.1049/iet-rpg.2015.0120
|View full text |Cite
|
Sign up to set email alerts
|

Scenarios for use of floating photovoltaic plants in Brazilian reservoirs

Abstract: The conversion efficiency of a crystalline silicon photovoltaic (PV) module increases as its temperature decreases. Considering this characteristic of the PV technology, in this study the authors analyse the use of cooled floating PV modules in a fraction of the area occupied by three reservoirs-Castanhão, Orós and Banabuiúin the Brazilian semi-arid region. Comparing with conventional ground-mounted PV modules, an average conversion efficiency increase of 12.5% was measured for floating PV modules under the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(34 citation statements)
references
References 19 publications
0
30
0
4
Order By: Relevance
“…However, as the cost of PV modules themselves have dropped a low-tilt angle system enables closer packing of modules (e.g., higher power per unit area) and can increase the solar electricity generated per unit area at an airport. In addition, for airports with surface water, floating solar PV farms [15][16][17][18][19][20][21] and even aquavoltaics [22] would enable an increased area for PV, as well as possibly reducing water surface glare.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as the cost of PV modules themselves have dropped a low-tilt angle system enables closer packing of modules (e.g., higher power per unit area) and can increase the solar electricity generated per unit area at an airport. In addition, for airports with surface water, floating solar PV farms [15][16][17][18][19][20][21] and even aquavoltaics [22] would enable an increased area for PV, as well as possibly reducing water surface glare.…”
Section: Resultsmentioning
confidence: 99%
“…Much of this need can be met via rooftop PV or the relatively immature building-integrated PV (BIPV) market [5][6][7][8][9][10]. The remainder will need to be met by large-area solar PV farms on either land-based solar PV farms [11][12][13][14] or even water-based floating solar PV farms [15][16][17][18][19][20][21][22]. However, as the global population increases 1.15% per year [23], attractive land and even waterways will become more valuable, especially in densely populated areas.…”
Section: Introductionmentioning
confidence: 99%
“…A fraction of three selected reservoir was occupied by the system for the study and the results flashed an increase in average conversion efficiency of 12.5%. PVSYST software was used to construct the electric production scenario which on comparison showed that energy produced by the PV system when spread over the entire area of the three reservoirs will be 18.8% of the electricity demand of its largest city Fortaleza [23] . A 100 kWp capacity floating solar PV system has been proposed for Loktak Lake, Manipur.…”
Section: Fspv Systems Across the Globementioning
confidence: 99%
“…For a large-scale PV system, a wide installation site should be ensured, however, this is difficult to achieve. Hence, the floating PV system, which is installed on the surface of water [1], is being tested in Korea. It can be a good alternative to solve the problem of securing the site by installing a PV system on a reservoir, for example [2,3].…”
Section: Introductionmentioning
confidence: 99%